A Web-Based Self-Management Program for Recent Combat Veterans With PTSD and Substance Misuse: Program Development and Veteran Feedback. Issue 3 (August 2015) - Possemato, Kyle; Acosta, Michelle C.; Fuentes, Juanita; Lantinga, Larry J.; Marsch, Lisa A.; Maisto, Stephen A.; Grabinski, Michael; Rosenblum, Andrew
Abstract Combat veterans from the wars in Iraq and Afghanistan commonly experience posttraumatic stress disorder (PTSD) and substance use problems. In addition, these veterans often report significant barriers to receiving evidence-based mental health and substance use care, such as individual beliefs that treatment will be unhelpful, inconvenient, or that they should be able to handle their problems on their own. To increase access to treatment for this underserved population, a Web-based patient self-management program that teaches cognitive-behavioral therapy (CBT) skills to manage PTSD symptoms and substance misuse was developed. This paper describes and provides results from an iterative, multistage process for developing the Web-based program and seeks to inform clinicians in the field about the preferences of veterans for using a Web-based CBT program. Systematic feedback was gathered from (a) three expert clinicians in the field, (b) focus groups of combat veterans (n = 18), and (c) individual feedback sessions with combat veterans (n = 34). Clinician feedback led to the incorporation of motivational strategies to increase participant engagement and an optional module that guides written trauma exposure work. Focus group feedback guided the research team to frame the program in a strength-based approach and allows for maximum flexibility, adaptability, interactivity, and privacy for veterans. In individual feedback sessions, veterans generally found the program likable, easy to use, and relevant to their experiences; critiques of the program led to revised content meant to increase clarity and participant interest. Our findings provide specific guidance for clinicians who are interested in developing or providing technology-based treatment, including the need to gather feedback from an intervention's target audience when adapting a psychotherapeutic intervention and that the treatment must be highly interactive and private to engage clients.